Managerial communication : evaluating the right dose - Johnson, J. David (New York, NY : Business Expert Press, 2012)
The metaphor of dosage offers a rich organizing principle for managers. It focuses our efforts on such fundamental, pragmatic communication issues as amount, frequency, delivery system, sequencing, interaction with other agents, and contraindications. It suggests compelling new answers to fundamental problems that all managers must face, with an appreciation of basic issues beyond our conscious awareness. The book is targeted toward graduate, executive, and professional audiences. In our day-to-day lives--whether we are discussing things with our housing contractor, our cable repair man, our doctor--we must constantly decide how much communication we should engage in to pursue our projects. This work focuses on the dosage metaphor as a way of confronting this question--what level of communication, both in terms of amount and of depth, is really necessary to accomplish particular purposes? Most communication theories implicitly paint a picture of the prevalence and paramount importance of communication, with a'communication metamyth' that more is necessarily better. This book provides the first truly comprehensive treatment of dosage. It also focuses on perhaps the most contemporaneously interesting issues of change and of productivity. The final chapter presents the dosage metaphor in broad sweep, suggesting a countervailing minimalist approach to communication.
Includes bibliographical references and index.
Keywords: Communication in management